Metformin attenuates carotid neointimal hyperplasia by modulating the vascular smooth muscle cell phenotype transformation through upregulation of TET2, Nur77 and calponin - Lin, Hao; Cheng, Shuo; Yuan, Zhichao; Yan, Zhiqiang; Zhang, Jifa (Archives of Biological Sciences, 2021)
Paper description: Metformin is used to treat type 2 diabetes based on its cardiovascular safety. Metformin modulates the proliferation and migration of vascular smooth muscle cells (VSMCs), but the underlying mechanisms are unclear. Metformin inhibited VSMC proliferation and migration and upregulated the expression of Nur77, TET2 and calponin in vitro, it increased the expression of Nur77, TET 2 and calponin, and reduced the the number of PCNA+ cells and the expression of MMP-9, preventing neointima hyperplasia in the carotid artery in the balloon injury model in vivo. This study provides a concept for a strategy for metformin use for treating cardiovascular diseases. Abstract: Metformin is a drug used to treat type 2 diabetes based on its effectiveness as well as cardiovascular safety. Metformin has been shown to modulate proliferation and migration of vascular smooth muscle cells (VSMCs), but the underlying mechanisms of the effect of metformin on VSMC function remains unclear. We found that metformin inhibits VSMC proliferation and migration and upregulates the expression of nuclear receptor subfamily 4 group A member 1 (Nur77), ten-eleven translocation 2 (TET2), and calponin in vitro. In the carotid artery balloon injury model of rats, metformin effectively prevented neointima hyperplasia in the carotid artery, including neointimal thickness, increased neointimal area, and the neointimal area/medial area ratio. It also reduced the number of proliferating cell nuclear antigen (PCNA)+ cells and increased the expression of Nur77, calponin and alpha-smooth muscle actin (α-SMA). These results show that metformin attenuates neointimal hyperplasia in balloon-injured carotid arteries via increased expression of TET2, Nur77 and calponin, and reduced expression of matrix metallopeptidase 9 (MMP-9).